2011
DOI: 10.1016/j.dcn.2011.02.004
|View full text |Cite
|
Sign up to set email alerts
|

fMRI of syntactic processing in typically developing children: Structural correlates in the inferior frontal gyrus

Abstract: Development of syntactic processing was examined to evaluate maturational processes including left language lateralization functions and increased specialization of brain regions important for syntactic processing. We utilized multimodal methods, including indices of brain activity from fMRI during a syntactic processing task, cortical thickness measurements from structural MRI, and neuropsychological measures. To evaluate hypotheses about increasing lateralization and specialization with development, we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(70 citation statements)
references
References 41 publications
9
61
0
Order By: Relevance
“…During development, both mental-attentional capacity limits and learned automatisations grow with age; thus lateralisation elicited by tasks should be relative to both age and task characteristics. Further, as Nunez et al 16 found 'children with thicker cortex in the right IFG (inferior frontal gyrus) rely less on right hemisphere language areas to process linguistic/syntactic information, relying more on left hemisphere processing than children with thinner cortex in the same brain regions.' Thicker grey matter in typical children's cortex is likely to express immaturity, whereas thinner areas may indicate that the learning-contingent maturational pruning has taken place 25 -i.e., local processing has matured.…”
Section: General State Of Developmental Cognitive Neurosciencementioning
confidence: 96%
See 1 more Smart Citation
“…During development, both mental-attentional capacity limits and learned automatisations grow with age; thus lateralisation elicited by tasks should be relative to both age and task characteristics. Further, as Nunez et al 16 found 'children with thicker cortex in the right IFG (inferior frontal gyrus) rely less on right hemisphere language areas to process linguistic/syntactic information, relying more on left hemisphere processing than children with thinner cortex in the same brain regions.' Thicker grey matter in typical children's cortex is likely to express immaturity, whereas thinner areas may indicate that the learning-contingent maturational pruning has taken place 25 -i.e., local processing has matured.…”
Section: General State Of Developmental Cognitive Neurosciencementioning
confidence: 96%
“…15 Similarly, thinner right inferior frontal cortices are linked to increased right inferior frontal activation in children and adolescents. 16 However, in a larger sample of adolescents no relation is observed between cortical and functional maturation-with authors cautioning against pre-assuming such an association. 17 To make matters more interesting, hemispheric involvement is not easily predictable in children; for instance, in response to cognitive tasks children and adolescents show less refined and less lateralised patterns than adults in one study 18 and similar lateralisation patterns to adults in another.…”
Section: General State Of Developmental Cognitive Neurosciencementioning
confidence: 99%
“…The results showed a significant overlap for syntactic and semantic processing. For older children, Nuñez et al (2011) found a relation between syntactic proficiency and activation in the left IFG, superior frontal gyrus (SFG), and middle frontal gyrus (MFG) independent of age. Moreover, in Englishspeaking children at the age of 7;2 to 15;8, they observed that the amount and extent of activation within the right IFG during syntactic processing (versus rest) was negatively correlated with cortical thickness in this region, which suggests a shift from the right to the left hemisphere during this age.…”
Section: Introductionmentioning
confidence: 98%
“…However, the studies in children often failed to find significant results at the group level, indicating a high variance in language proficiency that is not related to a specific age. Rather, several studies found that activation in the left IFG correlated with individual language skills (Nuñez et al, 2011;Yeatman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation